Evolution of urban models in a mediterranean coastal area. An effective aproach for delimiting urban typologíes - Castro Noblejas, Hugo; Orellana Macías, José María; Mérida-Rodríguez, Matías Francisco (My University, 2021)
Aims The Western Costa del Sol (Malaga, Spain) has been developed as a very dynamic environment since the middle of the s. XX. Its landscape is characterized by the intense anthropization derived from tourism and the consequent urbanization. The physical environment variety and the different ways of human occupation have generated a wide range of urban typologies, which lead to a diverse landscape. Since the landscape is one of the main assets of this coastal area, the aims of the present work are (a) to categorize the urban typologies, (b) to identify the predominant construction models in each period, and (c) to relate each urban typology with socioeconomic variables. Methods In the present work, the different stages of the urbanization process of Marbella (Spain) are characterized based on some of the most representative variables of urban habitability, such as vegetation density, construction density, road density, building height and distance to the urban core. Data obtained from the official Spanish Cadastre and remote sensing were treated by spatial analysis tools to create layers, which combined with socioeconomic variables and date of construction are able to delimit urban typologies. The relationship between each urban typology and the socioeconomic level of the inhabitants is also explored. This approach allowed us to accurately distinguish and map urban typologies at a municipality scale. Several periods since the mid-twentieth century were distinguished and mapped. Each period had specific urban characteristics, which are also connected to a certain socioeconomic level and a landscape value. Conclusion Different predominant typologies are recognized in the different recent stages of Marbella and they directly influence it urban landscape. The proposed procedure is a useful tool to accurately assess changes in urban areas, so it may be used in landscape assessment research.
Keywords: Urbanismo; Costal del Sol (Málaga); Ordenación del territorio; Geografía humana; Urban areas; Spatial patterns; Urban growth; Costa del Sol